Análise da inserção das plantas alimentícias não convencionais (PANC) na merenda escolar do município de Marechal Deodoro, Alagoas - Amorim, Paloma Sena (2025)
Non-Conventional Edible Plants (PANC) are edible plants that are not commonly part of the daily diet for most of the population but have high nutritional potential and are integral to the cultural traditions of various communities. This study analyzed the feasibility of incorporating PANC into the school meals of Marechal Deodoro (AL) and developed educational materials to disseminate the findings. The research adopted a descriptive approach, combining quantitative and qualitative methods, including bibliographic research, field research, and case studies. Data were analyzed using electronic spreadsheets and action research, allowing for the integration of analysis and practical application. The results showed that 65% of participants were unfamiliar with the term "PANC," yet 54% already consumed parts of these plants, demonstrating practical knowledge despite lacking familiarity with the terminology. All participants expressed interest in cultivating PANC, and 100% were willing to expand their production. Additionally, 83% reported learning about PANC through popular wisdom, highlighting the importance of traditional knowledge. Based on these findings, an educational material featuring recipes was developed to encourage the introduction of PANC into school meals, promoting nutritional awareness and strengthening local food practices.